Adolescents’ Conflicts: the Aspect of Values and Tendency of Conflicting Action - Čiuladienė, Gražina (Acta Paedagogica Vilnensia, 2006)
The article seeks to bring out peculiarities of adolescents’ conflicting action when their contradictors become classmates, teachers and parents, and to analyse the level of the frustration of teenager’s values. The type of investigating adolescents’ conflicts is determined by the values’ conflict. It was defined in the article as conflict caused by their, classmates, teachers, parents’ behaviour, frustrating adolescents’ values. Three types of conflicting teenagers’ behaviour is determined in the research: 1) aggressive treatment, 2) egressive treatment, 3) regressive treatment. The investigation was carried out with the 586 pupils aged from 12 to 16 years (7th-9th grades), learning in town, regional and country Lithuanian secondary schools. The link between adolescents’ conflicting action and frustration of adolescents’ values is established. According to data analysis, the conflicting action with classmates and teachers is mostly dealing with adolescents’ values such as love, responsibility, politeness frustration. Such values’ as love and friendship frustration is the most closely connected with adolescents’ conflicting action with parents. It has also been established that the values’ frustration mostly influences the aggressive adolescents’ behaviour. The results of the empirical research show that such values as love, freedom and seeking education are mostly frustrated. According to data analysis, there are 14.2 percent of pupils who feel deep frustration - lacking love; 8.6 percent – lacking freedom, 7 percent – lacking learning skills.